Identification of a variant antigenic neutralizing epitope in hypervariable region 1 of avian leukosis virus subgroup J. Issue 11 (8th March 2016) - Hou, Minbo; Zhou, Defang; Li, Gen; Guo, Huijun; Liu, Jianzhu; Wang, Guihua; Zheng, Qiankun; Cheng, Ziqiang
Highlights: Antibody induced by predicted B-cell multi-epitope protein can neutralize and recognize three different strains of ALV-J. A variant antigenic neutralizing epitope was identified using reverse vaccinology methods. The founder epitope and its variants can react with all anti-ALV-J sera from field, indicating the potential value for the novel multi-epitope vaccine development. Abstract: Avian leukosis virus subgroup J (ALV-J) is a hypervariable oncogenic retrovirus that causes great economic loss in poultry. Antigenic variations in the variable regions make the development of an effective vaccine a challenging task. In the present study, we identified a variant antigenic neutralizing epitope using reverse vaccinology methods. First, we predicted the B-cell epitopes in gp85 gene of ALV-J strains by DNAman and bioinformatics. Fourteen candidate epitopes were selected and linked in tandem with glycines or serines as a multi-epitope gene. The expressed protein of multi-epitope gene can induce high-titer antibody that can recognize nature ALV-J and neutralize the infectivity of ALV-J strains. Next, we identified a high effective epitope using eight overlapping fragments of gp85 gene reacting with mAb 2D5 and anti-multi-epitope sera. The identified epitope contained one of the predicted epitopes and localized in hyervariable region 1 (hr1), indicating a variant epitope. To better understand if the variants of the epitope have a good antigenicity, we synthesized four variants to react with mAb 2D5 and anti-ALV-J sera. The result showed that all variants could react with the two kinds of antibodies though they showed different antigenicity, while could not react with ALV-J negative sera. Thus, the variant antigenic neutralizing epitope was determined as 137-LRDFIA /E /T KWKS /G DDL /H LIRPYVNQS-158. The result shows a potential use of this variant epitopes as a novel multi-epitope vaccine against ALV-J in poultry.